Investigação e misticismo em Richard Zimler e outros escritores cabalistas - Marcos Fabio Cardoso de Faria (2014)
This dissertation studies, by means of analyzing Richard Zimlers The Last Kabbalist of Lisbon, the detective and the cabalist characters. Focusing on the possible encounter between investigation and mysticism proposed by the authors oeuvre, we seek to establish in this research a comparison-based methodology among characters, texts and authors. It is expected, among other aims, to delineate what could be a fictional genealogy for the investigator, prior to the institutionalized landmark to provide the ground for the crime story, that is, Edgar Allan Poes The murders of the Rue Morgue. Through this study, the conception of a detective-cabalist may expand the concept of text as a labyrinth, especially when the crime story takes on, as a temporary borrowing in its construction, notions of Jewish mysticism.